Optical transmission through MDM plasmonic tri-layer consisting of T and L shape periodic structures. Issue 1 (1st January 2021) - Dhyani, A.; Bhatia, K.S.; Sharma, Sudesh; Tewari, B.S.; Mandal, P.
Abstract : Optical transmission properties of plasmonic MDM (metal–dielectric–metal) tri-layer consisting of T and L shape periodic slit structures are investigated by finite difference time domain method. The spectral transmission in the range of visible to NIR (near-infrared) frequencies greatly depends on the slit structure. For T shape structure, single resonant transmission peak is observed, while L shape structure shows double resonance behaviour. The present study shows how structural shapes and polarizations of incident light determine the resonant condition. Based on the observed transmission spectra, an LC circuit model is presented. The low-frequency resonant peak is observed to be sensitive to the structural shape. The presence of side channel oriented parallel to the polarization direction of the input beam is responsible for the origin of high-frequency band (visible-end) in "L" shape structure. The present plasmonic structure is useful in optical transmissive devices.